2016
DOI: 10.1002/elan.201600032
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Pretreatment of Graphene Composite CNT Encapsulated Au Nanoparticles for H2O2 Sensor

Abstract: 1Introduction chemical impedance spectroscopy(EIS).T he nanocomposite displays intensive electrocatalytic activity towards the reduction of H 2 O 2 by enhancing the cathodic peak current and completely eliminatingt he interference of other species.T he AuNPs/PPG/CNT sensors howed an excellent amperometric response to H 2 O 2 reduction with linear range from 1.0-150 mMa nd detectionl imit of 0.017 mM. Moreover, the sensor showed good reproducibility as well as anti-interfering ability and long term stability.I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Dopamine (DA), vitamin C (VC), Alanine (Ala), Glutamic acid (Glu), uric acid (UA), glycine (Gly), folic acid (FA), acetaminophen (AC), graphite, 1,5-diaminonaphthalene ( Graphene was synthesized applying the procedures reported in the previous method [50]. Then, 0.5 % of GNS solution was prepared in DMF solvent and sonicated for about 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopamine (DA), vitamin C (VC), Alanine (Ala), Glutamic acid (Glu), uric acid (UA), glycine (Gly), folic acid (FA), acetaminophen (AC), graphite, 1,5-diaminonaphthalene ( Graphene was synthesized applying the procedures reported in the previous method [50]. Then, 0.5 % of GNS solution was prepared in DMF solvent and sonicated for about 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Dopamine (DA), vitamin C (VC), Alanine (Ala), Glutamic acid (Glu), uric acid (UA), glycine (Gly), folic acid (FA), acetaminophen (AC), graphite, 1,5‐diaminonaphthalene (1,5‐DAN), monobasic of sodium phosphate (NaH 2 PO 4 ), dibasic of sodium phosphate (Na 2 HPO 4 ), HNO 3 , H 2 SO 4 , [Ru(NH 3 ) 6 ]Cl 3 , KMnO 4 , K 3 [Fe(CN) 6 ], H 2 O 2 and K 4 [Fe(CN) 6 ] obtained by Sigma Co. (USA). Graphene was synthesized applying the procedures reported in the previous method [50]. Then, 0.5 % of GNS solution was prepared in DMF solvent and sonicated for about 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Because, Gr itself seems to be an electroinactive material, various methods were performed to improve Gr activity either through electrochemical reduction or using reductant substances . In this context, the electrochemical reduction of Gr was carried out not only to increase the electrochemical activity of Gr surface, but also to introduces an active sites on Gr structure .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gr composite metals nanoparticles could be suggested as potential candidates because of its abundant of oxygen groups that promote the electron transfer process between target analyte and electrode surface. Thus, metals nanoparticles doped Gr have been applied in order to increase the electrocatalytic activity of H 2 O 2 sensors, such as Pt, Au, ZnO, CoO, MnO 2 . Among of them, platinum nanoparticles (PdNPs) were used for designing different H 2 O 2 sensors due to its interesting properties, such as high conductivity and electrocatalytic activity that enhance the electron transfer process of H 2 O 2 as well as reduce the reduction overpotential .…”
Section: Introductionmentioning
confidence: 99%
“…28 The formed 3D nanostructures not only inherit the virtues of CNTs and graphene, but also provide extraordinary physicochemical, mechanical and electrical properties. [28][29][30][31][32][33] For instance, the composite of multi-walled carbon nanotubes (MWCNTs) and graphene oxide (GO) has been used to construct sensing interface for simultaneous measurement of sunset tartrazine and Yellow by Lu's group, it is found that the electrodes show an enhanced electrochemical response due to the synergistic catalysis of GO and CNTs. 32 Wang et al have fabricated an effective electrochemical biosensor for carbaryl determination by covalently immobilizing acetylcholinesterase on MWCNTs/GO nanoribbons.…”
Section: Introductionmentioning
confidence: 99%